ETHICS IN OPERATIONS MANAGEMENT: A LITERATURE REVIEW FROM A MULTIDISCIPLINARY PERSPECTIVE - Yanita; T. Hasinta Melani; Neza Lestari Putri; Nailah Salsabila; Sabila Zuina; Masyithah; Fauzan Jordi (CV. Radja Publika, 2025)
This article presents a comprehensive literature review integrating six scholarly works related to ethics in operations management. The review encompasses various perspectives, including business ethics and corporate social responsibility (CSR), organizational culture, Islamic business ethics principles, case studies on ethical operational practices in small and medium enterprises (SMEs), and the influence of Artificial Intelligence (AI) on operational efficiency. The research employs a systematic literature review method by analyzing articles from reputable academic sources. The findings indicate that ethics plays a significant role in improving operational performance, strengthening public trust, enhancing organizational culture, supporting business sustainability, and minimizing operational risks. Additionally, the implementation of AI demonstrates substantial efficiency improvements but requires careful ethical governance related to privacy, data security, and social impact. Overall, ethics in operations management is a crucial component that influences organizational effectiveness and long-term sustainability.